2020
DOI: 10.3390/ijerph17124256
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient Visits among Older Adults Living Alone in China: Does Health Insurance and City of Residence Matter?

Abstract: This study aimed to examine the association between health insurance, city of residence, and outpatient visits among older adults living alone in China. A sample of 3173 individuals was derived from “Survey on Older Adults Aged 70 and Above Living Alone in Urban China” in five different cities. Logistic regression models indicated that older adults living alone who had urban employee basic medical insurance, urban resident basic medical insurance, and public medical insurance were more likely to have outpatien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
(56 reference statements)
0
6
0
Order By: Relevance
“…However, despite having close family or friends, older adults still seem to prefer to overcome difficulties on their own rather than seek help, in order to avoid being a burden to others [24][25][26][27]. Older adults who are at an advanced age, live alone, with financial difficulties and no medical insurance, and have lower participation in community activities are likely to have a lower utilization of social support due to lack of information and a limited range of activities [18,19,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…However, despite having close family or friends, older adults still seem to prefer to overcome difficulties on their own rather than seek help, in order to avoid being a burden to others [24][25][26][27]. Older adults who are at an advanced age, live alone, with financial difficulties and no medical insurance, and have lower participation in community activities are likely to have a lower utilization of social support due to lack of information and a limited range of activities [18,19,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…In China, residents aged 35+ years would have their blood pressure assessed by doctors at their visits to hospitals or primary care centers since 2012 (10). Meanwhile, it has been documented consistently that the favorable health insurance scheme may increase the likelihood for people to seek health service at hospitals or primary care centers in China (11)(12)(13)(14)(15)(16)(17)(18)(19)36). Thus, beneficiaries with the favorable health insurance scheme (e.g., UEBMI in our study) were more likely to visit hospitals or primary care centers for seeking health service, and consequently had their blood pressure measured by doctors, and then had hypertension diagnosed by a doctor if they had the condition.…”
Section: Discussionmentioning
confidence: 99%
“…In such a case, individuals with HTN can be diagnosed as early as possible. Interestingly, health insurance has been investigated to be positively associated with visit to hospitals/ primary care centers among residents, particularly urban inhabitants in China (11)(12)(13)(14)(15)(16)(17)(18)(19). Moreover, health insurance was also examined in a positive relation to diagnosis of HTN for age-specific adults in USA and China (20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al investigated the relationships among health insurance, city of residence, and outpatient visits among the elderly living alone in China and found that those who had basic medical insurance for urban employees, basic medical insurance for urban residents, and public medical insurance could easily make outpatient visits compared to older adults living alone without health insurance [34]. After controlling for the number of chronic diseases, only those with public health insurance were more likely to visit a clinic than those without insurance.…”
Section: A Medical Insurance Systemmentioning
confidence: 99%